The Aesthetics of the Morphological , Syntactic and Metrical Terms in Abul Ala al-Múarri's Luzumiyat - Mahdi Masbuq; Mahdi Masbuq; Ali Bager Taherinia; Mahdi Torkashvabd (دراسات في اللغة العربيّة وآدابها)
Â Following the Flourishing of the "translation movement" during Abasid period , there was a rise in the use of scientific terms in poetry . Poets such as al-Motanabbi , Abu Tammam , al-MÃºarri and Abul Fath al-Basti used scientific expressions in their poetry because of their acquaintance with scientific Fields . AsÂ  al-MÃºarri enjoyed vost knowledge of various scientific fields , he generously used many terms from those fields in his work especially in his Luzumiyat (Unnecessary Necessities) . An upsurge in the use of these terms met the miyed reaction of the critics and scholars . Some lauded this Practice some expressed their disapproval . However , it seems the critics have failed to consider the aesthetic aspedts of these terms and expressions in MÃºarri's poetry . Obviously , investigation into these expreosions and communicative signs reveals the poet's ideas . Moreover , it shows the depth of his familiarity with scientific domains and richness of his poetry . The present article embarks on or investigation into the use of syntactic morphological and metrical terms by this poet , a task which he accomplished in a subtle and artistic way . It is dUe to this subtlety that understandiy his intended meaning takes the reader much reflection and contemplation on these terms in the Luzumiyat .Â